Предмет: Алгебра,
автор: Аноним
х+2=√х+4
√10+х - √х+3 = √4х-23
очень срочно, заранее большое спасибо
Ответы
Автор ответа:
0
х+2=√(х+4)
Возведём обе части ур-ия в квадрат
x^2+4x+4=x+4
x^2+4x-x=0
x^2+3x=0
x(x+3)=0
x=0
x=-3 ⇒ посторонний корень
ОТВЕТ: 0
√(х+10) - √(х+3) = √(4х-23)
Возведём обе части ур-ия в квадрат
x+10-2√(x+10)(x+3)+x+3=4x-23
2x+13-2√(x+10)(x+3)=4x-23
-2√(x+10)(x+3)=2x-36
√(x+10)(x+3)=18-x
Возведём обе части ур-ия в квадрат
x^2+13x+30=x^2-36x+324
13x+36x=324-30
49x=294
x=6
ОТВЕТ: 6
Автор ответа:
0
1)x^2+4x+4=x+4 одз:x>=-4
x(x+3)=0
x=0 x=-3(не удв)
2) 10+x-2sqrt(x^2+13x+30)+x+3=4x-23
-2sqrt(x^2+13x+30)=2x-36
sqrt(x^2+13x+30)=18-x
x^2+13x+30=x^2-36x+324
49x-294=0
x=6
Похожие вопросы
Предмет: Математика,
автор: roksanaismagulova20
Предмет: Қазақ тiлi,
автор: moldabekovanazym123
Предмет: Математика,
автор: 10HelpMePlease01
Предмет: Математика,
автор: PrO100чебурек